Ultrasonographic and Dopplerfluxometria Assessment of Renal Function in Pyometra-Affected Bitches - Kuttikkattuparambil Thilak, Hitha; Mooloor Harshan, Hiron; Choppillil, Jayakumar; Aravind, Amritha; Chempanpathalil Gopalan, Umesh (The Indian Journal of Animal Reproduction, 2025)
Pyometra is a complex diestrual disorder that primarily affects the uterus in mature bitches and can have systemic effects on various organs and physiological systems. One of the main complications observed with this disease is its renal affection. Though detection of renal impairment has been traditionally done by evaluating serum biochemical values or urinary biochemical results; analysis of renal size and perfusion employing ultrasonography and Dopplerfluxometria offer new means of analysis. The aim of this study was to evaluate the renal function in pyometra affected bitches employing the traditionally used serum and urinary parameters as well as ultrasonographic and Dopplerfluxometria assessment. Thirteen bitches affected with pyometra and six healthy bitches, kept as control, were used in the study. The animals were assessed for renal injury by evaluating serological parameters such as blood urea nitrogen (BUN) and creatinine; urinary protein to creatinine ratio (UPCR) and renal ultrasonographic evaluation and Dopplerfluxometria. It was noted that Dopplerfluxometria of renal artery offered evidence of renal damage in instances where serological, urinary and renal size assessments failed to detect any indications of renal impairment in pyometra affected bitches.